KOMODIFIKASI WARGA DALAM RUANG CITIZEN JOURNALISM - Nasrullah, Rulli (Jurnal Kawistara, 2012)
The citizen journalism has been inïuenced not only by organization culture of media and news criteria, but also the position of citizens. This entire time citizens are merely a consumers and their position is passive to information produced by traditional media. With the emergence of citizen journalism, now the citizens not only become news consumers but also act as news producers and consumers at the same time (produsage). The commodiïcation of citizen journalism is a phenomenon of counter commidiïcation done by the companies of traditional media. This shown that there are symptoms of attracting each other in the room (market) of citizen journalism that the citizens do not always react passively to the exposure of media and become a commodity by traditional media companies or the advertiser, but they also commodify anything as whatever they want to reach. Thus, this research is a rebutting the deïnition of citizen journalism popularized by Curt Chandler and Jesse Hicks from Penn State University who said that citizen journalism is citizens activities in publishing a content because of their interest to a case without economic motive or personal gain.